2017
DOI: 10.1021/acs.chemrev.7b00344
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Copper Active Sites in Zeolites and Their Correlation to Metalloenzymes

Abstract: Metal-exchanged zeolites are a class of heterogeneous catalysts that perform important functions ranging from selective hydrocarbon oxidation to remediation of NO pollutants. Among these, copper and iron zeolites are remarkably reactive, hydroxylating methane and benzene selectively at low temperature to form methanol and phenol, respectively. In these systems, reactivity occurs at well-defined molecular transition metal active sites, and in this review we discuss recent advances in the spectroscopic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
349
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 291 publications
(356 citation statements)
references
References 242 publications
(954 reference statements)
5
349
0
2
Order By: Relevance
“…Thel ow amount of side products prevented their quantification in the gas phase. However,the analysis of the reacted material and the product by IR and nuclear magnetic resonance (NMR) spectroscopy showed that CH 3 O-species,a long with trace amounts of HCOO-and CO,w ere formed upon reaction with CH 4 ,a s confirmed by 13 CH 4 isotope studies (Supporting Information, Figures S19-S21). Them aterial 2-a 700 had as imilar performance (9 %CH 3 OH yield and 23 %Cureduction with 75% of electrons involved in CH 3 OH formation (Supporting Information, Table S2, Figure S22).…”
Section: Angewandte Chemiementioning
confidence: 83%
See 3 more Smart Citations
“…Thel ow amount of side products prevented their quantification in the gas phase. However,the analysis of the reacted material and the product by IR and nuclear magnetic resonance (NMR) spectroscopy showed that CH 3 O-species,a long with trace amounts of HCOO-and CO,w ere formed upon reaction with CH 4 ,a s confirmed by 13 CH 4 isotope studies (Supporting Information, Figures S19-S21). Them aterial 2-a 700 had as imilar performance (9 %CH 3 OH yield and 23 %Cureduction with 75% of electrons involved in CH 3 OH formation (Supporting Information, Table S2, Figure S22).…”
Section: Angewandte Chemiementioning
confidence: 83%
“…[6] These enzymes,containing Cu or Fe metal centers,have inspired the design of materials for the conversion of CH 4 to CH 3 OH under mild reaction conditions. [9][10][11][12][13] Thes tructure of the active site is highly debated, with evidence for both (m-oxo) dinuclear copper [9,14] and tris(moxo) trinuclear copper centers (Figure 1a). This hurdle can, in principle,b eo vercome using the concept of chemical looping,w hich entails decoupling the steps of oxidation of Cu sites and their reaction with CH 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ad rastic enhancement in the reactivity of the cupric superoxide towards phenolic substrates as well as oxidation of substrates possessing moderate C À Hb ond-dissociation energies is observed, correlating with the number and strength of the H-bonding groups.Oxidation and oxygenation reactions are vital for biological and synthetic processes. [1][2][3][4][5][6][7][8][9] In biology,s ome copper-containing metalloenzymes are capable of performing these reactions. [2,10] Forexample,galactose oxidase (GO) is responsible for the oxidation of primary alcohols to aldehydes (Figure 1A); monooxygenases such as peptidylglycine a-hydroxylating monooxygenase (PHM), dopamine b-monooxygenase (DbM), and lytic polysaccharide monooxygenases (LMPOs) catalytically hydroxylate organic substrates containing strong (85-100 kcal mol À1 )C ÀHb ond dissociation energies (BDEs) using dioxygen ( Figure 1B).…”
mentioning
confidence: 99%